The phenomenon of agencification in the administration of the European Union - Kühn, Werner Miguel (Journal of the Belarusian State University. International Relations, 2021)
The article offers an analysis of the process known as agencification that has led the EU to rely on numerous agencies in order to fulfill its administrative tasks. The focus lies on the status of these agencies within the EU legal system, the way in which they are established, their internal organization and financing, the decision-making procedures, as well as their operation. Furthermore, a classification of the agencies is carried out by using specific categories. It also explains the challenges that agencies face in their daily activities. It explains their relationship with the EU institutions, especially with regard to the democratic control and the control of legality that the latter exercise.
Keywords: integration process; law of regional economic integration; supranational administration; European agencies; European Union; European Economic Area; Area of Freedom, Security and Justice